Optimasi Ukuran Penampang pada Struktur Rangka Batang Ruang dengan Binary Dragonfly Algorithm - Richard Frans; Stevy Thioritz (Jurnal Manajemen Teknologi & Teknik Sipil, 2023)
The cross-section area of a structural element plays a vital role in designing and planning processes. Each structural element must meet design criteria while maintaining an effective cross-sectional area, ensuring the structure is economical and lightweight. This Economic aspect refers to the structure's cost and weight, minimizing any lateral effects that may arise. This research aimed to determine the optimum cross-sectional for bamboo elements, with the objective of minimizing the weight of the space truss structure but still meets the design criteria. Four different cross-sectional areas of bamboo were used, 4272,566 mm2, 3382,71 mm2, 3084,259 mm2, and 2827,433 mm2. The optimization algorithm used is the binary dragonfly algorithm. There are two configurations of space truss structures considered, the first space truss structure is 25 members, and the second space truss is 32 members (pyramid module). The program was run four times to ensure the convergence and consistency of the results obtained. The results show that the weight of the first space truss structure is 86.98 kg while the weight of the second space truss structure is 64.6015 kg. The results can be considered optimal as the critical element's actual stress is close to the allowable stress. Therefore, the binary dragonfly algorithm can be an alternative method to optimize the cross-sectional area of structural element especially for space truss structure.